Yield Performance of Chia (Salvia Hispanica L.) In Response to Planting Spacing and Npk Fertilizers (Bangladesh Agronomy Journal, 2023)
Optimization of plant spacing, and fertilizer dose is very important for realizing maximum yield of a crop. An experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh during November 2020 to March 2021 to determine the effect of different spacing and NPK fertilizer levels on yield and yield attributes of chia seed. The experiment consisted of four different spacing viz. 30 cm × 15 cm (S1), 30 cm × 30 cm (S2), 40 cm × 15 cm (S3) and 40 cm × 30 cm (S4) and five levels of NPK fertilizer viz. No NPK (F0), 30: 20: 25 kg NPK ha-1 (F1), 60: 40: 50 kg NPK ha-1 (F2), 90: 60: 75 kg NPK ha-1 (F3) and 120: 80: 100 kg NPK ha-1 (F4). The experiment was laid out in a factorial randomized complete block design (RCBD) with three replications. The results revealed that 40 cm × 30 cm spacing produced the highest number of inflorescences plant-1, seed yield and haulm yield. The fertilizer level 90: 60: 75 kg NPK ha-1 showed the highest seed yield and haulm yield while 120:80 :100 kg NPK ha-1 exhibited the maximum number of inflorescences plant-1. The combination of 30 cm ×30 cm spacing and 90: 60: 75 kg NPK ha-1 produced the highest number of inflorescences plant-1 and seed yield whereas the combination of 40 cm × 30 cm spacing and 90: 60: 75 kg NPK ha-1 had the highest haulm yield. The present study concluded that cultivation of chia at a spacing of 30 cm × 30 cm and fertilized with 90: 60: 75 kg NPK ha-1 could be considered as the promising practice for reasonable seed yield.Bangladesh Agron. J. 2023, 26(1): 122-127